Michel de Certeau's Daily Life in the Ordinary Management Practices of a Civil Society Organization in Caruaru, Pernambuco - Morais, Wilson Mike; Santos, Elisabeth Cavalcante dos (Organizações & Sociedade, 2024)
Based on the notion of everyday life proposed by Michel de Certeau, the research aimed to understand how the ordinary management practices of a civil society organization in Caruaru, Pernambuco are constituted. We use the concept of "ordinary management" as we seek to understand how the entity's management occurs, indeed, beyond formalized processes. We also discuss Michel de Certeau's concept of "ordinary everyday life", composed of heterogeneous operations in which subjects use strategies and tactics for their production and reproduction. We used participant observations, documentary research, and semi-structured interviews to operationalize the research. The findings were treated through the hermeneutic triad of narrative analysis highlighted by Barbara Czarniawska. We accessed seven everyday practices that allowed us to realize that strategies and tactics are continually mobilized when building the CSO's ordinary management. We highlight that participatory and decentralized management and popular education are the central premises of CSO management and that the study of ordinary management allows us to understand how these premises build the organization's daily life. We also noted conflicts, power relations, and hierarchies relating to the places and spaces occupied by the entity.